Community embodiment of memory: un-doing trauma (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article examines the way in which the community as a body reenacts past events in the bodies of their members displayed on the scene and reflects on its impact on social, artistic, and political relations. It analyzes the forms and functions that this practice gives to the body. It thinks about how it triggers social processes of memory that intervene and revive the past so as to provide the members and their environment with a new historical consciousness. It studies the way in which it releases the bodies from the postures adopted due to the absorption of the civilizing pattern that has formed them in their gestures, modes and languages, reinforcing social positions and limiting their political possibilities. This corporal memory, by becoming aware and modifying itself, gives the subjects the possibility of adopting unallocated functions and roles, thus expanding their role as social agents.